Mock humanity : James Ensor's grotesques and the History of Caricature by Jules Champfleury : frame and figure in the work of James Ensor - Verschaffel, Bart (A&S/Books, 2018)
This book reveals that James Ensor did not develop his fantastic and grotesque universe of masks and skeletons out of his melancholic soul, but that he re-used and transformed an old image tradition that was collected and published by the French author and art critic Jules Champfleury in his 'History of Caricature'. A second essay analyses how these weird creatures infiltrate the image borders and the frames of Ensor's paintings in order to disturb the 'normal' world